2004
DOI: 10.1016/j.eupc.2004.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal atrial fibrillation in male endurance athletes. A 9-year follow up

Abstract: A small proportion of the athletes (26%) was asymptomatic. Paroxysmal atrial fibrillation remained stable in half of the athletes whereas the arrhythmia changed into permanent atrial fibrillation in a minority of this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 23 publications
3
62
1
Order By: Relevance
“…350,351 Indeed, AF is the primary arrhythmia observed in middle-aged athletes. 352 AF in athletes tends to be paroxysmal, vagally mediated, and highly symptomatic.…”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%
See 1 more Smart Citation
“…350,351 Indeed, AF is the primary arrhythmia observed in middle-aged athletes. 352 AF in athletes tends to be paroxysmal, vagally mediated, and highly symptomatic.…”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%
“…350 Professional athletes represent a unique treatment dilemma because medical therapy for AF might not only reduce athletic performance but it could also be prohibited in some sports. 369 …”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%
“…Although few data support the concept that limitation of sports activities can have favourable outcomes in athletes with AF, 16,42 it is advisable to look for cases where arrhythmia may be a manifestation of excessive engagement in sports training. In these cases, a period of detraining for three months to achieve and maintain sinus rhythm is advocated, while the degree of improvement during this resting period will determine whether athletes are allowed to resume their training.…”
Section: Management Of Atrial Fibrillation In Athletesmentioning
confidence: 99%
“…A study by Hoogsteen et al showed that lone AF did not demonstrate a severe evolution and is well-tolerated in most athletes. 42 It is also essential, before proceeding to specific therapies for AF, to exclude and treat appropriately other possible causes of the arrhythmia, such as hyperthyroidism, myocarditis, pericarditis, WPW syndrome, channelopathies and hypertrophic cardiomyopathy, as well as alcohol consumption and use of illicit sympathomimetic substances.…”
Section: Management Of Atrial Fibrillation In Athletesmentioning
confidence: 99%
“…[14][15][16] First, they are typically young or middle-aged adults and have practiced endurance sports for several years. Several studies [9][10][11][12][13] indicate that young or middle-aged athletes who had undergone longterm high intensity training have the highest incidence of AF. Second, it is more prevalent in male than female athletes.…”
Section: Characteristics Of Af In Athletesmentioning
confidence: 99%